Big Brother ‘Titans’ Show and Cable Subscription: A Case Study of GOTV Subscribers in Uyo - Udoudom, Uduak Imoh; Pam, Christiana Chundung; Igiri, Anthony Bassey (International Journal of Humanities, Education, and Social Sciences, 2023)
This study explored the impact of the popular reality TV show, Big Brother 'Titans', on cable subscriptions among GOTV subscribers in Uyo. A survey questionnaire was distributed among a representative sample of 322 GOTV subscribers in Uyo, focusing on their viewership habits, motivations for subscribing to GOTV, and the influence of Big Brother 'Titans' on their subscription decisions. The findings revealed that Big Brother 'Titans' has a significant impact on the cable subscription patterns of GOTV subscribers in Uyo. The majority of respondents reported watching the show regularly and acknowledged that it was a primary reason for their subscription. The captivating nature of the show, coupled with its interactive elements and the sense of community it fostered, emerged as key motivators for maintaining their GOTV subscriptions. The study concluded that "Big Brother Titans" show has become a major draw for viewers, prompting them to opt for cable subscriptions that offer access to the show. This demonstrates the power of compelling content in shaping consumer behavior and influencing market dynamics. Furthermore, the study recommended that GOTV should offer flexible subscription packages: This can include the ability to add or remove channels based on individual preferences. By allowing subscribers to customize their cable package, they can ensure access to the Big Brother Titans show without being constrained by unnecessary channels or costs.